Effects of Metamizole, 4-Methylaminoantipyrine, and 4-Aminoantipyrine on LX-2 Liver Cell Line Viability and Apoptosis - Georgiana-Iulia Lupu; Emoke Pall; Mihai Cenariu; Monica Irina Nan; Sanda Andrei (Molecules)
Metamizole (dipyrone) is a non-opioid analgesic widely used in human and veterinary medicine, despite ongoing concerns about its safety due to risks such as agranulocytosis and potential hepatotoxicity. This study investigates the cytotoxic (MTT assay) and pro-apoptotic effects of metamizole and its primary metabolites, 4-methylaminoantipyrine (4-MAA) and 4-aminoantipyrine (4-AA), on the LX-2 liver cell line. These metabolites are implicated in both the therapeutic and adverse effects of the drug. The objective is to elucidate the mechanisms of potential hepatotoxicity, with a focus on cell viability and apoptosis. Metamizole was tested at five concentrations (100, 200, 400, 600, and 1000 µg/mL), while its metabolites were tested at two concentrations (100 and 1000 µg/mL). The results show a dose-dependent decrease in cell viability, with significant reductions at higher concentrations. The greatest cytotoxic effects were observed with 4-AA and 4-MAA, which induced marked apoptosis at 1000 µg/mL. This study concludes that metamizole and its metabolites can cause liver cell damage, underscoring the importance of caution in its clinical use and the need for further research to ensure its safety.